2018
DOI: 10.1103/physrevb.98.214513
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional order parameter induced by helical chiral molecules adsorbed on a metal proximity coupled to a superconductor

Abstract: Following our previous results, which provide evidence for the emergence of a chiral p-wave tripletpairing component in superconducting Nb upon the adsorption of chiral molecules, we turned to investigate whether such an effect can take place in a proximal superconductor consisting of metal on superconductor bilayer. Note that in such proximity systems, correlated electron-hole (Andreev) pairs exist in the normal metal rather than genuine Cooper pairs. To that end, we used scanning tunneling spectroscopy (STS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 62 publications
(77 reference statements)
4
29
0
Order By: Relevance
“…Most models for such topological phases demand a uniform ferromagnetic ordering; a condition that probably does not occur in our system considering the drop cast method we used to form the molecular monolayers. Indeed, our previous STM/STS studies 22,23 of chiral molecules adsorbed on Nb and Au/NbN films showed that the adsorption is not uniform and homogeneous all over the surface, although we did find islands of uniformly aligned molecules within an overall disordered molecular layer (including moleculefree regions). A similar disordered adsorption configuration was revealed also in our present STM measurements on the surface of a cleaved NbSe2 crystal (e.g., inset of Fig.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Most models for such topological phases demand a uniform ferromagnetic ordering; a condition that probably does not occur in our system considering the drop cast method we used to form the molecular monolayers. Indeed, our previous STM/STS studies 22,23 of chiral molecules adsorbed on Nb and Au/NbN films showed that the adsorption is not uniform and homogeneous all over the surface, although we did find islands of uniformly aligned molecules within an overall disordered molecular layer (including moleculefree regions). A similar disordered adsorption configuration was revealed also in our present STM measurements on the surface of a cleaved NbSe2 crystal (e.g., inset of Fig.…”
mentioning
confidence: 58%
“…This is consistent with our previous results, described in refs. 22,23 and discussed above, suggesting that the introduction of chiral molecules modifies the order-parameter.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, colloidal assembly provides an economical way of structural color development and plays an important role in fabrication of stopband materials, optic devices, sensing materials, etc., thus drawing much interest. [ 11–25 ] Among them we mainly focus on the latex assembly affording either long‐range‐order crystalline lattices or short‐range‐order glassy arrays, thus providing stable structures highly controllable within a relatively wide (ultraviolet, visible, and infrared regions) range of stopbands. Typically, colloidal assembly involves the spreading of a latex suspension onto a substrate followed by solvent evaporation‐induced latex nucleation and crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the predicted effect has been observed with chiral molecules adsorbed on various substrates. For example, it has been shown that chiral molecules adsorbed onto s-wave superconductors induce triplet superconductivity [32][33][34], or Shiba-like states [34]. Chiral molecules on ferromagnetic surfaces induce magnetic ordering [35,36].…”
mentioning
confidence: 99%